First hydrothermal discoveries on the Australian‐Antarctic Ridge: Discharge sites, plume chemistry, and vent organisms. (15th September 2015) - Hahm, Doshik; Baker, Edward T.; Siek Rhee, Tae; Won, Yong‐Jin; Resing, Joseph A.; Lupton, John E.; Lee, Won‐Kyung; Kim, Minjeong; Park, Sung‐Hyun
Abstract The Australian‐Antarctic Ridge (AAR) is one of the largest unexplored regions of the global mid‐ocean ridge system. Here, we report a multiyear effort to locate and characterize hydrothermal activity on two first‐order segments of the AAR: KR1 and KR2. To locate vent sites on each segment, we used profiles collected by Miniature Autonomous Plume Recorders on rock corers during R/V Araon cruises in March and December of 2011. Optical and oxidation‐reduction‐potential anomalies indicate multiple active sites on both segments. Seven profiles on KR2 found 3 sites, each separated by ∼25 km. Forty profiles on KR1 identified 17 sites, some within a few kilometer of each other. The spatial density of hydrothermal activity along KR1 and KR2 (plume incidence of 0.34) is consistent with the global trend for a spreading rate of ∼70 mm/yr. The densest area of hydrothermal activity, named "Mujin, " occurred along the 20 km‐long inflated section near the segment center of KR1. Continuous plume surveys conducted in January–February of 2013 on R/V Araon found CH4/3He (1 − 15 × 106) and CH4/Mn (0.01–0.5) ratios in the plume samples, consistent with a basaltic‐hosted system and typical of ridges with intermediate spreading rates. Additionally, some of the plume samples exhibited slightly higher ratios of H2/3He and Fe/Mn than others, suggesting that those plumes are supported by a younger hydrothermal system that may have experienced a recent eruption. The Mujin‐field was populated by Kiwa crabs and seven‐armed Paulasterias starfish previously recorded on the East Scotia Ridge, raising the possibility of circum‐Antarctic biogeographic connections of vent fauna.